Alicia the Snow Queen fairy - Meadows, Daisy (New York : Scholastic, Inc., 2017)
When Jack Frost steals Alicia the Snow Queen Fairy's magical objects, Rachel and Kirsty help Alicia.
4.7
3-6
720L
Keywords: Fairies -- Fiction; Magic -- Fiction; Fairies -- Fiction; Magic -- Fiction; Fantasy fiction